A study on neurotransmitter levels in rats with Tic disorder treated with aripiprazole - Chen, Hui-Min; Wang, Yang; Xin, Ying-Ying; Sun, Dan; Yang, Xue; Liu, Zhi-Sheng (Frontiers in Neuroscience, 2025)
BackgroundTic disorder (TD) involves dysregulation of neurotransmitters. Although aripiprazole (ARI) is a first-line therapy, its mechanism remains debated, and animal studies are limited. This study investigates ARI's effects on neurotransmitter levels in a rat TD model.MethodsForty male Sprague-Dawley rats were randomly assigned to five groups of eight animals each: control group, TD untreated group, and low/medium/high dose ARI groups (1.6/4/10 mg/kg). With the exception of the control group, all rats underwent modeling with 3,3'-iminodipropionitrile (IDPN) for seven consecutive days.Following modeling, the ARI groups were administered different doses of ARI via gavage for 2 consecutive weeks. The control group and TD untreated group received equivalent volumes of saline. Behavioral tests were conducted upon completion of the modeling phase and again following the 2-week gavage period. Changes in neurotransmitter levels in rat plasma and striatum were detected using ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS).Receiver operating characteristic (ROC) curve analysis was performed on neurotransmitters showing statistically significant differences to evaluate their diagnostic efficacy for TD.Results(1) Compared with the TD untreated group, all ARI dose groups showed lower motor and stereotypic behavior scores after the 14-day gavage period. (2) As shown by UPLC-MS/MS, the TD untreated group had significantly lower glutamate (Glu) and γ-aminobutyric acid (GABA) levels in plasma, yet higher levels in the striatum, when compared to the control group. (3) Following ARI intervention, a marked reduction in striatal Glu and GABA levels was observed across all dose groups, and the Glu/GABA ratio showed a dose-dependent reduction. (4) ROC analysis revealed that plasma Glu and GABA alone had moderate predictive efficacy; striatal Glu and GABA demonstrated superior predictive performance. When combined for prediction, the AUC for plasma neurotransmitters was 0.848, and for striatal neurotransmitters, it was 0.938.ConclusionARI can regulate motor and stereotypic behaviors in TD rats and effectively control tic symptoms. TD rats exhibit dysregulation of Glu and GABA levels, and ARI can modulate Glu and GABA levels, thereby improving neurotransmitter function. Furthermore, central neurotransmitter changes demonstrate superior diagnostic value over peripheral measures for TD.